Pengaruh Kompres Bawang Merah Terhadap Penurunan Suhu Tubuh Pada Kejadian Ikutan Paska Imunisasi (KIPI) Pentabio - Reni Pebriani; Lisda Handayani; Hairiana Kusvitasari (Jurnal Rumpun Ilmu Kesehatan, 2023)
Shallots (Allium cepa variety ascalonicum) can be used as a fever-reducing medicine in infants and toddlers with fever. Infants with fever after Pentabio immunization is about 60% and the way to reduce fever after Pentabio immunization in infants so far is by giving pharmacological therapy, namely antipyrectic syrup (paracetamol syrup). The purpose of this study was to determine the effect of onion compress on reducing body temperature in the incidence of pentabio post-immunization follow-up (KIPI). The research method is an experimental quasy method with pretest and posttest approaches. The samples used accidental sampling technique, namely 12 infants who had been given pentabio immunization in January 2023 at PMB Hj. F Kotabaru. Data collection using questionnaires analyzed in the form of frequency distribution. The results showed that most of the babies who had a fever before being given onion compresses were 12 people (92.3%), babies who did not have fever after compressing shallots as many as 10 people (83.3%). The implication of the results of the study is that compresses using red onions are an effective alternative to reduce fever in infants.